News in Early Modern Europe Currents and Connections - Davies, Simon; Fletcher, Puck (Library of the Written Word - The Handpress World, 2014)
News in Early Modern Europe presents new research on the nature, production, and dissemination of a variety of forms of news writing from across Europe during the early modern period. Readership: Postgraduate and undergraduate students, researchers, and academic libraries, from the fields of history and literature, with interests in early modern Europe, news, book history, literary forms, social history, and politics.